2001
DOI: 10.1128/jcm.39.11.4119-4124.2001
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Serotype- and Group-Specific Fluorogenic Reverse Transcriptase PCR (TaqMan) Assays for Dengue Virus

Abstract: Five fluorogenic probe hydrolysis (TaqMan) reverse transcriptase PCR (RT-PCR) assays were developed for serotypes 1 to 4 and group-specific detection of dengue virus. Serotype-and group-specific oligonucleotide primers and fluorogenic probes were designed against conserved regions of the dengue virus genome. The RT-PCR assay is a rapid single-tube method consisting of a 30-min RT step linked to a 45-cycle PCR at 95 and 60°C that generates a fluorogenic signal in positive samples. Assays were initially evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(155 citation statements)
references
References 19 publications
2
147
0
6
Order By: Relevance
“…The amount of viral RNA present in samples was determined using the Superscript III One-Step Quantitative RT-PCR System (qRT-PCR; Invitrogen, Carlsbad, CA) with a Light Cycler 480 system (Roche, Mannheim, Germany) using methods described elsewhere. 47 A standard curve method was used to relate the amount of DENV RNA present in samples to 10-fold serial dilutions of virus stock with known concentrations expressed in pfu per milliliter. 48,49 Mosquitoes were categorized based on status of infection: disseminated infections, positively infected bodies and legs; non-disseminated infections, infected bodies but the absence of virus in legs; and uninfected, absence of virus in the body.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of viral RNA present in samples was determined using the Superscript III One-Step Quantitative RT-PCR System (qRT-PCR; Invitrogen, Carlsbad, CA) with a Light Cycler 480 system (Roche, Mannheim, Germany) using methods described elsewhere. 47 A standard curve method was used to relate the amount of DENV RNA present in samples to 10-fold serial dilutions of virus stock with known concentrations expressed in pfu per milliliter. 48,49 Mosquitoes were categorized based on status of infection: disseminated infections, positively infected bodies and legs; non-disseminated infections, infected bodies but the absence of virus in legs; and uninfected, absence of virus in the body.…”
Section: Methodsmentioning
confidence: 99%
“…The same fluorescence combination format has been applied for detection of DENV-1 to -4 in serum specimens from patients with dengue fever (4,14). The combination of universal primer pairs with four virus-specific probes simplifies the optimization step (4; this study); in contrast, other multiplex designs require four unique primer pairs and four different probes (2,14). Another significant improvement is the development of an in vitro-transcribed RNase-resistant RNA template for use as the copy number control.…”
Section: Vol 45 2007mentioning
confidence: 99%
“…The real-time PCR assay has many advantages over conventional RT-PCR methods, including lower contamination rate, higher sensitivity and specificity, and they are rapid, providing results in minutes instead of hours. Several investigators have reported the use of real-time PCR assays for detecting some viral causes of hemorrhagic fevers (Drosten et al, 2002a), including Ebola (Gibb et al, 2001;Towner et al, 2004;Weidmann et al, 2004), Rift Valley fever (Garcia et al, 2001), and dengue (Laue et al, 1999;Callahan et al, 2001;Houng et al, 2000) viruses. Drosten et al (2002a) developed a one-step real-time RT-PCR assay for detecting CCHFV using primers to the nucleoprotein gene; however, they used the DNA-intercalating dye, SybrGreen I, for detecting the PCR product because no conserved binding site for a 5 -nuclease probe could be found.…”
Section: Molecular Diagnostic Assaysmentioning
confidence: 99%